A corpus‐based analysis of adjective amplification in Hong Kong, Indian and Philippine English - Schweinberger, Martin (World Englishes, 2025)
This study considers a corpus‐based approach for analysing adjective amplifier systems (very, really, so, etc.) in Hong Kong English (HKE), Indian Englsih (IndE) and Philippine English (PhiE) based on data from the International Corpus of English. The current study adds to existing research by providing insights into the understudied adjective amplifier systems of Asian Englishes. The study describes the amplifier systems in HKE, IndE and PhiE, and it ascertains if these amplifier systems are undergoing change. In the latter context, the analysis assesses if really or so is replacing very as the dominant adjective amplifier in these varieties—a trend shown to be at work in Inner Circle varieties of English. The results of Conditional Inference Trees show that the amplifier systems of HKE and IndE are very stable and amplifier choice in these varieties is determined predominately by intra‐linguistics factors (adjective type, syntactic context and semantic category). In contrast, the amplifier system of PhiE shows notable signs of ongoing change, which is driven predominately by social factors (age and gender of speakers). The results indicate that during stasis and initial stages of change, language‐internal factors determine amplifier choice, while social factors become more important once changes have reached the midrange. The paper argues that once certain variants (really and so) gain social meaning, it is this social meaning (the association with specific social groups) that drives and accelerates change as speakers want to associate with social groups that carry covert prestige.